The Importance and Value of Knowledge in the Religion of Islam - qizi, Saidova Latofat Hasan (Jurnal Pendidikan Islam, 2024)
This article discusses such questions as: what place is given to knowledge in the religion of Islam? What honorable place is given to literate people and teachers? And also it is about religious sciences and secular sciences, and that every Muslim in his life should strive to gain knowledge. The journal explores the critical role of knowledge in Islam. It highlights how Islam, as the true religion of Allah, emphasizes the acquisition of knowledge as essential for leading a righteous life. The teachings of the Holy Quran and the Prophet Muhammad (peace be upon him) underscore that a Muslim is responsible before Allah for all actions and must pursue knowledge to avoid error and find the true path. The Quran encourages reflection and knowledge acquisition, linking religious values and scientific understanding, emphasizing the harmony between religion and science. Islam views education as the foundation of personal and societal prosperity, where knowledge gained must be applied for the benefit of others. Teachers hold an esteemed place in Islamic society, as they shape individuals into wise, ethical, and productive members of society. The article concludes that education fosters human progress, and Muslims must respect teachers and continue striving for knowledge, which ultimately leads to personal growth and societal welfare.